Effectiveness and safety among direct oral anticoagulants in nonvalvular atrial fibrillation: A multi‐database cohort study with meta‐analysis. Issue 6 (16th December 2020) - Durand, Madeleine; Schnitzer, Mireille E.; Pang, Menglan; Carney, Greg; Eltonsy, Sherif; Filion, Kristian B.; Fisher, Anat; Jun, Min; Kuo, I. Fan; Matteau, Alexis; Paterson, J. Michael; Quail, Jacqueline; et al.
Abstract : Aims: There are conflicting signals in the literature about comparative safety and effectiveness of direct oral anticoagulants (DOACs) for nonvalvular atrial fibrillation (NVAF). Methods: We conducted multicentre matched cohort studies with secondary meta‐analysis to assess safety and effectiveness of dabigatran, rivaroxaban and apixaban across 9 administrative healthcare databases. We included adults with NVAF initiating anticoagulation therapy (dabigatran, rivaroxaban or apixaban), and constructed 3 cohorts to compare DOACs pairwise. The primary outcome was pooled hazard ratio (pHR) of ischaemic stroke or systemic thromboembolism. Secondary outcomes included pHR of major bleeding, and a composite of stroke, major bleeding, or all‐cause mortality. We used proportional hazard Cox regressions models, and pooled estimates were obtained with random effect meta‐analyses. Results: The cohorts included 73 414 new users of dabigatran, 92 881 of rivaroxaban, and 61 284 of apixaban. After matching, the pHRs (95% confidence intervals) comparing rivaroxaban initiation to dabigatran were: 1.11 (0.93, 1.32) for ischaemic stroke or systemic thromboembolism, 1.26 (1.09, 1.46) for major bleeding, and 1.17 (1.05, 1.30) for the composite endpoint. For apixaban vs dabigatran, they were: 0.91 (0.74, 1.12) for ischaemic stroke or systemic thromboembolism, 0.89 (0.75, 1.05) for major bleeding, and 0.94 (0.78 to 1.14) for the composite endpoint. For apixaban vs rivaroxaban, they were: 0.85 (0.74, 0.99) for ischaemic stroke or systemic thromboembolism, 0.61 (0.53, 0.70) for major bleeding, and 0.82 (0.76, 0.88) for the composite endpoint. Conclusion: We found that apixaban use is associated with lower risks of stroke and bleeding compared with rivaroxaban, and similar risks compared with dabigatran.